Multifunctional Transition Metal‐Based Phosphides in Energy‐Related Electrocatalysis - Li, Yang; Dong, Zihao; Jiao, Lifang (Advanced energy materials, 2020)
The exploitation of cheap and efficient electrocatalysts is the key to make energy‐related electrocatalytic techniques commercially viable. In recent years, transition metal phosphides (TMPs) electrocatalysts have gained a great deal of attention owing to their multifunctional active sites, tunable structure, and composition, as well as unique physicochemical properties. This review summarizes the up‐to‐date progress on TMPs in energy‐related electrocatalysis from diversified synthetic methods, ingenious‐modulated strategies, and novel applications. In order to set forth theory–structure–performance relationships upon TMPs, the corresponding reaction mechanisms, electrocatalytsts' structure/composition designs and desired electrochemical performance are jointly discussed, along with demonstrating their practical electrocatalytic applications in overall water splitting, metal–air batteries, lithium–sulfur batteries, etc. In the end, some underpinning issues and research orientations of TMPs toward efficient energy‐related electrocatalysis are briefly proposed. This review summarizes the recent modulated strategies of transition metal phosphides upon elemental doping, interfacial regulation, phase modification, structural engineering, and nanocarbon incorporation. Benefitted from the optimized structure and composition, transition metal phosphides (TMPs) display excellent performance in electrocatalytic hydrogen evolution reaction, oxygen evolution reaction, oxygen reduction reaction, CO2 reduction reaction, etc., along with their practical applications in water electrolyzer, metal–air batteries, and lithium–sulfur batteries, etc.